Treatment challenges in and outside a network setting: Head and neck cancers. Issue 1 (January 2019) - ,; Hackl, Monika; Eycken, Elizabeth Van; Henau, Kris; Dimitrova, Nadya; Sekerija, Mario; Dušek, Ladislav; Mägi, Margit; Malila, Nea; Leinonen, Maarit; Velten, Michel; Troussard, Xavier; et al.
Abstract: Head and neck cancer (HNC) is a rare disease that can affect different sites and is characterized by variable incidence and 5-year survival rates across Europe. Multiple factors need to be considered when choosing the most appropriate treatment for HNC patients, such as age, comorbidities, social issues, and especially whether to prefer surgery or radiation-based protocols. Given the complexity of this scenario, the creation of a highly specialized multidisciplinary team is recommended to guarantee the best oncological outcome and prevent or adequately treat any adverse effect. Data from literature suggest that the multidisciplinary team-based approach is beneficial for HNC patients and lead to improved survival rates. This result is likely due to improved diagnostic and staging accuracy, a more efficacious therapeutic approach and enhanced communication across disciplines. Despite the benefit of MTD, it must be noted that this approach requires considerable time, effort and financial resources and is usually more frequent in highly organized and high-volume centers. Literature data on clinical research suggest that patients treated in high-accrual centers report better treatment outcomes compared to patients treated in low-volume centers, where a lower radiotherapy-compliance and worst overall survival have been reported. There is general agreement that treatment of rare cancers such as HNC should be concentrated in high volume, specialized and multidisciplinary centers. In order to achieve this goal, the creation of international collaboration network is fundamental. The European Reference Networks for example aim to create an international virtual advisory board, whose objectives are the exchange of expertise, training, clinical collaboration and the reduction of disparities and enhancement of rationalize migration across Europe. The purpose of our work is to review all aspects and challenges in and outside this network setting planned for the management of HNC patients.